PENGARUH HARGA DAN ATRAKSI WISATA TERHADAP KEPUASAN WISATAWAN DI MUSEUM MAGIC ART 3D (DIMENSI) KOTA TUA JAKARTA - Larasati Utami; Nova Eviana (LPPM and Travel Operation Department Universitas Asa Indonesia, 2019)
Visitor satisfaction is very closely related to the quality of tourism products, including tourist attractions and prices. Alluring tourist attractions will provide a memorable experience for visitor, and impact on revisit intention or recommendation to others. Competitive prices and great experience gained affect tourist satisfaction. This research aimes to determine the influence of prices and tourist attractions on tourist satisfaction at the Magic Museum 3D (dimension) Jakarta. The survey research involves 100 museum visitors as respondents, using the accindental sampling technique. Data are then analyzed by multiple linear regression. The result shows that prices and tourist attractions have a 20.61% contribution toward tourist satisfaction at the Magic Art 3D (dimension) museum Jakarta. It is therefore important for museum managers to keep developing the variety of tourist attractions to be more attractive and competitive as well pricing strategy.